Distribution of blood groups in dogs of different breeds in Kyiv and Kyiv Oblast, Ukraine - Malyuk, M. O.; Honchar, V. V.; Klymchuk, V. V.; Kovalenko, D. O.; Onyshchenko, O. V.; Boiko, H. V.; Paramonova, Y. V. (Regulatory Mechanisms in Biosystems, 2025)
In veterinary transfusion medicine, correct identification of blood group of dogs is critical to prevent immunological compl i cations. The most clinically significant antigen is DEA 1 ( dog erythrocyte an tigen 1), which can cause sensitization and deve l opment of acute hemolytic reaction in recipients of repeated transfusion of incompatible blood. Taking into account the impo r tance of local mapping of the distribution of blood groups, the objective of this study was determining the distribution of the DEA 1 blood group in dogs of different breeds in Kyiv and Kyiv Oblast, emphasizing the analysis of breed variability and clinical significance of the results for veterinary practice. In the study, we used 493 blood samples from dogs whose owners contacted the clinic or the bank of animal blood during the period between 2018 and 2024. Blood group was identified using the immunoc h romatographic method with RapidVet-H Canine DEA 1 kits. All the samples were tested for the presence of DEA 1 antigen with the subsequent distribution according to breeds, calculation of the percentage ratio of DEA 1+ and DEA 1-, and also the statistical analysis with the χ² criterion in relation to the null hypothesis of even distribution (50/50). In general, 55.4% of the animals turned out to be DEA 1-positive, while 44.6% were found to be DEA 1-negative. We determined a significant variability in the distrib u tion of blood groups depending on the breed. The largest share of DEA 1+ was observed in the English Cocker Spaniels, Pom e ranian Dogs, and American Cocker Spaniels, while the DEA 1- blood group dominated in the German Shepherds, Belgian Shepherds, and Giant Schnauzers. The obtained results indicate a possible genetic tendency of certain breeds toward a particular blood type. The results are consistent with similar studies in other countries and can be used for designing effective programs of selecting donors in veterinary transfusion medicine. A special attention should be paid to the limited number of DEA 1- donors, which underscores the importance of pre-typing of blood before each transfusion. The study is the first large-scale analysis of the distribution of DEA 1 in dogs in Ukraine and therefore is of practical significance for the development o f clinical veterinary medicine.